Effects of regular physical activity on pain, anxiety, and depression in patients with treatment-resistant arterial hypertension - Kruk, Piotr Jan; Nowicki, Michał (Family Medicine & Primary Care Review, 2016)
Background . Medical experts and professional societies commonly recommend regular physical activity to patients with arterial hypertension. However there is little evidence of the influence of physical exercise on treatment-resistant arterial hypertension. Objectives. The aim of the study was to analyze the influence of physical activity, intensified with additional training support, and followed up with SMS reminders regarding pain, anxiety, and depression in patients with resistant hypertension. Material and methods. The study group consisted of 53 patients, including 27 who fulfilled the criteria for resistant hypertension, and a control group of 26 patients with well-controlled blood pressure. Initially, 24-hour monitoring of blood pressure, anthropometric measurements, and measurements of body composition by means of electric bioimpedance were conducted after the third and sixth month, and a mobile activity profile was defined by means of accelerometric measurements conducted for subsequent 72 hours. The patients completed the Hospital Anxiety and Depression Scale (HA DS) and the Roland and Morris Disability Questionnaire (RMDQ). The patients were advised to perform regular aerobic physical activity in accordance with the guidelines of the American Heart Association. Results . After 6 months, the back pain score as assessed with RMDQ had reduced from 8.2 ± 7.5 to 6 ± 5.9 (p = 0.01) in subjects with treatment-resistant hypertension. Similar results applied to anxiety (score 8.2 ± 4 vs. 9.3 ± 4.4 at baseline; p = 0.02) and depression as measured with HA DS (5.3 ± 3 vs. 6.9 ± 3.7 at baseline; p = 0.01). There was a significant positive correlation between the changes in the pain score (RMDQ) and the changes in the 24 h and nighttime systolic blood pressure, pulse pressure, and anxiety. Conclusions . Regular physical activity may have a beneficial effect on anxiety, depression, and pain in patients with treatmentresistant hypertension.